The Understanding of Ancestral Veneration among the African and Vietnamese People - Hung, Francis Nguyen Thanh (Asian Horizons, 2020)
The cult of ancestors plays a significant role in the lives of African and Vietnamese people. The practice of ancestral veneration was one of the most controversial issues for early Christian missionaries especially in Africa and Asia. This article will argue that both the Africans and Vietnamese do not worship their ancestors. Both the Africans and Vietnamese recognize the existence of one God as the transcendental Being who is the subject of worship. Ancestral rituals and practices show the sense of community, solidarity, communion and fidelity with departed members. On the contrary, the ancestor cults in these places focus on remembering, honouring and loving their “living” dead or ancestors. Moreover, this paper will show how the indigenous Christian Churches in Africa and Vietnam find ways to reconcile their traditional concepts of ancestors with the message of Gospels. Finally, some lessons from the way African theologians are doing theology in their context could be used for doing theology in the Vietnamese context.